Organizational change management model proposal: action-research in a public exam company. - Serrano Filho, Eduardo de Souza; Junior, Jorge Muniz; Martins, Fernando Ramalho (Revista Gestão da Produção Operações e Sistemas, 2023)
Purpose – The presented research aimed to propose a model for organizational change management for a public examination company, which has experienced a significant increase in its activities and business environment in recent decades. Design/methodology/approach – The adopted methodological approach was action research. The collected data allowed for the identification of the dominant culture within the organization and the assessment of its internal and external environment. This information informed the selection of an appropriate change management model. Findings – Two results emerged from the research, one of general use and the other specific to the context: i. a method for choosing change management models, and ii. a detailed management model outlined for the analyzed organization. Originality/value – The academic contribution consisted of developing a method for searching and selecting a management model. It is noteworthy that this method itself represents an initial outcome of the research with a high level of applicability, not limited to companies in the public examination sector. Regarding the final product, the selected and detailed model's primary contribution lies in guiding the organization in making adjustments to remain competitive and continue its operations. The outlined steps include the necessary care and attention to details in implementing changes, aiming to effectively contribute to the success of the adaptations required by the market scenario. Keywords: Organizational change. Change management. Organizational culture.